A Proposal for a Method of the Redesign of Self-Organising Systems: The Case of Minibus Transportation in the Istanbul Public Transport System - Ekmekçioğlu, D.; Şen, M.Ö. (Universidade do Vale do Rio dos Sinos Av. Unisinos, 950 - Caixa Postal 275 Sao Leopoldo - RS CEP 93022-000, 2018)
The aim of this study was to propose a method for situations in which self-organising systems developed by creative communities are considered by the governing authorities. Self-organising systems form as a result of situations in which the basic needs of communities are inadequately met by the governing authorities. In the framework of this study, minibus transportation, a system organised by community stakeholders, was addressed as a design problem, and a redesign of the system was proposed to the governing authorities of the public transport service of Istanbul. Semi-ethnographic research was used to investigate the case study, and service design tools were used to transform the information obtained into data that was presented to the designers. The methodology consisted of three research stages: recognise the self-organising system, perform research concerning the co-experiences of system stakeholders, and determine design references for the governing authorities. As a result of the study, design references obtained by applying the proposed methodology were converted and evaluated by the designers as design solution proposals. © 2018 Universidade do Vale do Rio dos Sinos. All rights reserved.
Keywords: Co-Experience; Creative Communities; Self-Organising Systems; Transition Design